2021
DOI: 10.1038/s41467-021-25367-z
|View full text |Cite
|
Sign up to set email alerts
|

Tet2 Controls the Responses of β cells to Inflammation in Autoimmune Diabetes

Abstract: Abstractβ cells may participate and contribute to their own demise during Type 1 diabetes (T1D). Here we report a role of their expression of Tet2 in regulating immune killing. Tet2 is induced in murine and human β cells with inflammation but its expression is reduced in surviving β cells. Tet2-KO mice that receive WT bone marrow transplants develop insulitis but not diabetes and islet infiltrates do not eliminate β cells even though immune cells from the mice can transfer diabetes to NOD/scid recipients. Tet2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…We chose to infuse PBS or AAV8 into 4-week-old animals (Figure 6B) because our data showed that Mettl3 levels start to decline after this age in NOD females (Figure 1A and 1H). We confirmed Mettl3 protein overexpression at 12 weeks of age (Figure 6C) and followed these mice for up to 25 weeks of age similar to previous studies in the NOD mouse model (Kulkarni et al, 2021; Nelson et al, 2020; Rui et al, 2021). Body weight trajectories didn’t change until 17 weeks of age when mice that received AAV8 driving eGFP overexpression (AAV8-eGFP) or PBS started to lose weight compared to mice that received AAV8 driving Mettl3 overexpression (AAV8-Mettl3) (Figure 6D).…”
Section: Resultssupporting
confidence: 88%
“…We chose to infuse PBS or AAV8 into 4-week-old animals (Figure 6B) because our data showed that Mettl3 levels start to decline after this age in NOD females (Figure 1A and 1H). We confirmed Mettl3 protein overexpression at 12 weeks of age (Figure 6C) and followed these mice for up to 25 weeks of age similar to previous studies in the NOD mouse model (Kulkarni et al, 2021; Nelson et al, 2020; Rui et al, 2021). Body weight trajectories didn’t change until 17 weeks of age when mice that received AAV8 driving eGFP overexpression (AAV8-eGFP) or PBS started to lose weight compared to mice that received AAV8 driving Mettl3 overexpression (AAV8-Mettl3) (Figure 6D).…”
Section: Resultssupporting
confidence: 88%
“…Studies in NOD mice have been supportive of the notion that autonomous characteristics of β cells might allow for their evasion from immune attack ( Fenske et al, 2017 ; Lee et al, 2020 ; Rui et al, 2017 ; Thompson et al, 2019 ). Recently, inflammatory signaling by Tet2 within β cells has been proposed as a modifier of the immune response in NOD mice ( Rui et al, 2021 ). Because Tet2 is expressed in a host of immune cells, the definitive role of inflammatory signaling within β cells and its mechanism in mediating cellular crosstalk, however, remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, the former is characterized by the progressive destruction of pancreatic β cells, while the latter is characterized by peripheral insulin resistance. Although the pathogenesis of DM has been extensively studied, its treatment still focuses on glycemic control. Therefore, it is of great significance to develop new treatment strategies to solve this major public health problem.…”
Section: Introductionmentioning
confidence: 99%